2013
DOI: 10.1111/bor.12033
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of mean winter air temperatures in Siberian permafrost at 20−18 ka BP using oxygen isotope data

Abstract: Palaeotemperature reconstruction for the period of 20−18 ka BP in Siberia is here based on δ 18 O analysis and 14 C dating of large syngenetic ice wedges. Dozens of yedoma exposures, from Yamal Peninsula to Chukotka, have been studied. Snow meltwater is considered to be the main source of ice-wedge ice. The modern relationship between δ 18 O composition of ice-wedge ice and winter temperature is used as a base for reconstruction. In modern ice wedges (elementary veins that have accumulated during the last 60-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Existing δ 18 O—temperature relationships for ice wedges (Table ) are based on a spatial comparison of stable‐isotope data of modern ice veins and modern syngenetic ice wedges (ie, those formed during the last 60–100 years) and respective mean air temperatures from nearby meteorological stations. Streletskaya et al used only study sites with meteorological stations within 100 km and referred to 1961–90 as the reference period.…”
Section: Research Topics—state Of the Art And Future Research Prioritiesmentioning
confidence: 99%
“…Existing δ 18 O—temperature relationships for ice wedges (Table ) are based on a spatial comparison of stable‐isotope data of modern ice veins and modern syngenetic ice wedges (ie, those formed during the last 60–100 years) and respective mean air temperatures from nearby meteorological stations. Streletskaya et al used only study sites with meteorological stations within 100 km and referred to 1961–90 as the reference period.…”
Section: Research Topics—state Of the Art And Future Research Prioritiesmentioning
confidence: 99%
“…relative humidity, sea surface temperature) in the moisture source region (Merlivat and Jouzel, 1979). In the last years, stable-isotope data from ice wedges have been progressively used to reconstruct past climate changes in Arctic permafrost regions in northern Siberia (Meyer et al, 2002a(Meyer et al, , b, 2015Opel et al, 2011Opel et al, , 2017aWetterich et al, , 2014Vasil'chuk and Vasil'chuk, 2014;Streletskaya et al, 2015) as well as in Alaska (Meyer et al, 2010b;Lachniet et al, 2012;Schirrmeister et al, 2016) and in Canada (Fritz et al, 2012;Porter et al, 2016) on different timescales and with different temporal resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…Streletskaya et al . () and Vasil'chuk and Vasil'chuk () used δ 18 O values from ice wedges to reconstruct winter air temperatures. Modern January air temperature and the δ 18 O composition of modern ice wedges were compared in different Eurasian areas, to establish a linear regression.…”
Section: Ice Wedges and Ice‐wedge Casts For Palaeoenvironmental Reconmentioning
confidence: 99%
“…() reported late Weichselian January air temperatures of around ‐40 °C near Dikson in Taymyr, Siberia. Vasil'chuk and Vasil'chuk () indicated that mean winter air temperatures across Siberia were 8–12 °C lower during the Last Glacial Maximum (LGM) 18–20 ka BP than at present, based on regionally distributed δ 18 O and 14 C AMS dating of ice wedges, with a clear cooling eastwards.…”
Section: Ice Wedges and Ice‐wedge Casts For Palaeoenvironmental Reconmentioning
confidence: 99%
See 1 more Smart Citation